Simulation of the impact of an additional corrugated structure impedance on the bursting dynamics in an electron storage ring - S. Maier; M. Brosi; A. Mochihashi; M. J. Nasse; M. Schwarz; A.-S. Müller (Physical Review Accelerators and Beams)
In the case of a single-digit picosecond bunch length, synchrotron light sources produce intense coherent radiation up to the THz range. The reduction of the bunch length by lowering the momentum compaction factor (low-α) gives rise to the microbunching instability, which is on the one hand a crucial roadblock in the x-ray range during to the resulting effective bunch lengthening, but on the other hand also an opportunity for the generation of intense THz radiation if it can be controlled appropriately. In the KIT storage ring KARA (Karlsruhe Research Accelerator), two parallel plates with periodic rectangular corrugations are planned to be installed as a proof of principle in an electron storage ring. These plates create an additional longitudinal impedance based on their geometry, which can affect the beam dynamics. The resulting impedance manipulation will be used to study and control the longitudinal electron beam dynamics and the emitted coherent synchrotron radiation. This paper presents the results of systematic studies in simulation of the impact of additional corrugated plate impedances on the longitudinal beam dynamics using the example of the KARA storage ring. If the periodicity of the wake function of the corrugated plates matches the size of the substructures in the longitudinal bunch profile, the instability threshold can be effectively manipulated. This extends intense THz radiation to different beam current regimes.